2009
DOI: 10.1177/0021998309341847
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Model for Determining Tensile Strengths of Various Unidirectional Composites

Abstract: Simultaneous fiber-failure (SFF) model that determines tensile strengths for various systems of unidirectional composites comprehensively is presented. The SFF derives the strength of unidirectional composites as a function of the single-fiber strength distribution, interfacial shear strength, and matrix strength. The point of the SFF is that a fiber group which is considered to be experiencing simultaneous fiber failures triggered by neighboring fiber failures is assumed to fail when the weakest fiber in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…GLS is a statistical method that accounts for progressive fiber failure and subsequent fiber load redistribution by shear lag through the composite matrix . In the GLS model, the strength of a composite loaded in the fiber direction is controlled by the strength of the reinforcing fibers, which are statistically characterized by the Weibull distribution . Weibull parameters σ 0 , L 0 , and m , and the fiber‐matrix interfacial shear strength, τ, and the average fiber diameter, D , are used to estimate the composite strength as follows: σx,uC=VF×σc(m+1m+2)(2m+2)1/m+1 Where σ c is considered the critical fiber stress and is given by: σc=(2σ0mτL0D)1/m+1 …”
Section: Modeling Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GLS is a statistical method that accounts for progressive fiber failure and subsequent fiber load redistribution by shear lag through the composite matrix . In the GLS model, the strength of a composite loaded in the fiber direction is controlled by the strength of the reinforcing fibers, which are statistically characterized by the Weibull distribution . Weibull parameters σ 0 , L 0 , and m , and the fiber‐matrix interfacial shear strength, τ, and the average fiber diameter, D , are used to estimate the composite strength as follows: σx,uC=VF×σc(m+1m+2)(2m+2)1/m+1 Where σ c is considered the critical fiber stress and is given by: σc=(2σ0mτL0D)1/m+1 …”
Section: Modeling Methods and Resultsmentioning
confidence: 99%
“…The GLS model, which is known to overestimate the strength of many composites that exhibit damage localization, was modified to account for simultaneous fiber failure (SFF) initiated by a weak fiber within a group . The SFF model uses the interaction between the strengths of the fiber, matrix, and fiber–matrix interface to quantify a number of SFFs within an arbitrary region of the composite.…”
Section: Modeling Methods and Resultsmentioning
confidence: 99%
“…It has been reported that if the interface strength exceeds a specific value, the mechanical properties of composite material may deteriorate [1]. However, it is difficult to evaluate the interface strength conventionally [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of the interfacial stress transfer capacity causes the propagation of interfacial failure, and consequently, an increase in the stress recovery length around the fiber failure. This increase can be associated with a decrease in the strength of unidirectional composites [8][9][10][11][12]. Hence, the evolution of time-dependent interfacial failure can play a key role in ensuring the long-term durability of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [9], we integrated the frictional effect into the interfacial failure progression. In these articles [9][10][11][12][13][14][15][16], a time-dependent interfacial failure criterion plays a key role in precisely predicting the progression of interfacial failure. Several studies have shown that interfacial shear strength decreases with time [9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%